KELAYAKAN FLIPCHART PADA SUBMATERI PEMANFAATAN KENAKERAGAMAN HAYATI KELAS X SMA - Eka Jumarti; Syamswisna Syamswisna; Yokhebed Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to find out the feasibility of flipchart media in the benefits of Sub Material of The Utilization of Biodiversity for Senior High School tenth grader from three high schools. The method used in this study was qualitative research using the descriptive. Validation sheet was used as the instrument of research. Each statement item is divided into categories Very Good is worth 4, Good is worth 3, Less Good is worth 2, and Not Good is worth 1. Since the data is in qualitative form, then to calculate it needs to be converted into a quantitative form using the Lawshe formula. Validation results from the validator can be analyzed using Content Validity Ratio (CVR) analysis. The flipchart feasibility as a learning media was then being verified by two lecturers of Biology major in Faculty of Teachers Training and Education Tanjungpura University and three Biology teachers for Senior High School tenth grader from three high schools. Based on the verifier assessments, the flipchart are valid with CVI 0.99 and feasible to be used as learning media in the benefits of Sub Material of The Utilization of Biodiversity.Keywords: Biodiversity, Flipchart, Senior High School